Cleanliness Assessment of Sub-District in Regency Using Technique for Order Preference by Similarity to Ideal Solution - Thanh Nguyen, Phong; Herman, Herman; Thuy To Nguyen, Quyen Le Hoang; Wayan Suparta, I; Bich Huynh, Vy Dang (Opción, 2019)
Cleanliness is a human need to be healthy. In Tanggamus Regency the cleanliness still very lacking, but the government continues to strive so he cleanliness can be promoted by each district in Tanggamus. The problem in assessing cleanliness between sub districts in Tanggamus is very difficult. Because there are many sub-districts in the Tanggamus area, so there needs to be a system that can assist in the assessment. This Decision Support Sys- tem was made to assist the hygiene assessment process using the TOPSIS (Technique for Order Preference by Similarity to Ideal Solution) method by the Sanitation and Gardening Department (DKP). The existence of this system can help district employees in the assessment of cleanliness between sub district in Tanggamus regency.